THE ROLE OF THE MEDIA IN SHAPING AND PROPAGATING MAY DAY RITUALS: AN EXAMPLE OF GLAS SLAVONIJE, NEWSPAPER FROM OSIJEK (1945-1950) (Review of Croatian History, 2021)
The Communist Party of Yugoslavia’s (CPY) rise to power in 1945 was followed by a period of fundamental socio-political changes that encompassed all aspects of life. In order to establish a complete political and ideological authority, the government attempted to suppress all elements which, in their view, were not aligned with the doctrine of the Communist Party. As a result, everything that was perceived as remnants of the old socio-political order was marginalised, such as religion, tradition and customs. Moreover, reinterpretation of the past also took place, as well as creation of new rituals and Tito’s cult of personality. Accordingly, a completely new calendar of official, state holidays was established, deprived of any national or religious tradition. One of those holidays was May Day, which was celebrated for two days and whose purpose, like most other holidays of that period, was to create uniqueness of feelings and actions in society, focusing on the working class, socialism, CPY, Yugoslavia and Josip Broz Tito. Besides, celebrations of major anniversaries and holidays, including May Day, presented an opportunity for transmission of ideological and political messages, most often articulated through numerous slogans which clearly defined the direction in which the society should move. The media played a key role in this process. Therefore, the central part of the paper consists of the analysis of newspaper articles from Glas Slavonije in order to understand its role in the implementation of those new political rituals and social values.